If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -9 = 8x + 15 Reorder the terms: -9 + -4x = 8x + 15 Reorder the terms: -9 + -4x = 15 + 8x Solving -9 + -4x = 15 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -9 + -4x + -8x = 15 + 8x + -8x Combine like terms: -4x + -8x = -12x -9 + -12x = 15 + 8x + -8x Combine like terms: 8x + -8x = 0 -9 + -12x = 15 + 0 -9 + -12x = 15 Add '9' to each side of the equation. -9 + 9 + -12x = 15 + 9 Combine like terms: -9 + 9 = 0 0 + -12x = 15 + 9 -12x = 15 + 9 Combine like terms: 15 + 9 = 24 -12x = 24 Divide each side by '-12'. x = -2 Simplifying x = -2
| 10a+5=7 | | 3x+2=228 | | -9=-y | | -7*3x^3= | | q^3-2q^2=500 | | 11+5x=-14 | | 12M-6M+11=6M+16 | | -6(4p+4)-28=4(3p+5) | | y-15.53=-8.53 | | X+x-47770=296770 | | 6.5y=45.5 | | 2x-47770=296770 | | 2x=6+20 | | (d^4+2d^3-3d^2)y=x^2+3e^2x+4sinx | | 9/2x-3/2=15/2 | | 6-7n+4n=22-91 | | y-1=-7/8 | | X/.9=90 | | -68+3y+9=2(5y-2)-6 | | 3(4x-8)+7=12x-17 | | 6/5-5x=4 | | -5(6-5)-73= | | X-8.3=1.4 | | X+33.9=39.6 | | X-2.7=2.3 | | 3x-4x+9x= | | X+17.5=22.2 | | cx+3x= | | 5x+5y=215 | | X-4=20.6 | | 81x(1/2)^n | | 3(x-9)=(x-3) |